Analysis of Parking Space Requirements in Grand Galaxy Park Mall and Performance of Boulevard Raya Roads Jakasetia, Bekasi City - Dermawan, Widodo Budi; Imamsyah, Alif (Journal of World Conference (JWC), 2020)
Bekasi City is a large city with a population of 2,803,283 people (BPS, 2016). The area of ??Bekasi City is 210.49 km². Grand Galaxy Park Mall is one of the malls located in the city ??of Bekasi precisely on Boulevard Raya Roads Grand Galaxy City Jakasetia. The area is of land approximately 19.000 meters² with a floor area of 17.000 meters² which consists of 5 floors. Grand Galaxy Park Mall became one of the popular shopping centers because this mall is known as a modern mall and was built with an environmentally friendly concept and the location of this mall is also very strategic and integrated with the residential area of ??Grand Galaxy City, Schools, Shops and Offices. The method used in this research is the observation method. The Observation Method is a method by conducting direct survey of spaciousness. This is absolutely necessary to determine the actual condition. The survey method used in this analysis is the method of recording the number of vehicles. The largest accumulation of parking for cars on Saturday as many as 132 vehicles occurred between 18.00-18.59 WIB, while for motorcycles on Saturday as many as 167 vehicles occurred between 19.00-19.59 WIB. The average duration of vehicle parking is 3 hours 42 minutes for cars and 3 hours 30 minutes for motorbikes. The largest parking index is 85.16% for cars occurred on Saturday at 18.00-18.59 WIB and 41.75 for motorcycles occurred on Saturday at 19.00-19.59 WIB. The biggest Parking Turn Over is 4 vehicles / SRP / observation time for cars and 3 vehicles / SRP / observation time for motorcycles and that happens on Saturdays. Judging from the analysis of the Jalan Raya Raya Boulevard Jalan Jakasetia for the survey speed at peak hours in the morning, afternoon and evening get the level of service or Level of Service (LOS), namely B and C.